Pengaruh Reward terhadap Disiplin Kerja Dimediasi Kepuasan Kerja pada PT. Dipo Star Finance Padang - Zhafirah, Talitha; Yulihasri; Lukito, Hendra (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to examine the effect of rewards on work discipline, which is mediated by job satisfaction in employees of PT Dipo Star Finance Padang. A quantitative approach with hypothesis-testing techniques was used in this research. There were 92 samples using a saturated sampling technique, namely all employees of PT Dipo Star Finance Padang. Data was collected by distributing questionnaires online and processed using SmartPLS 4.0 software. The data analysis method uses structural equation modeling with partial least squares (SEM-PLS). The research results show that rewards have a positive and significant effect on job satisfaction and work discipline. Job satisfaction has a positive and significant effect on work discipline. Job satisfaction is able to partially mediate the relationship between rewards and work discipline. The implications of the research emphasize the importance of providing comfort to employees while working, in addition to providing appreciation in the form of rewards for employees with good performance, so that employees can comply with company rules in the future.